Quantification and Localization of Intracellular Free Mg2+ in Bovine Chromaffin Cells - Montezinho, Liliana P. (2002)
Magnesium is an essential element for all living systems. The quantification of free intracellular Mg(2+) concentration ([Mg(2+)](i)) is of utmost importance since changes in its basal value may be an indication of different pathologies due to abnormalities of Mg(2+) metabolism. In this work we used (31)P NMR and fluorescence spectroscopy to determine the resting [Mg(2+)](i) in bovine chromaffin cells, a neuron-like cellular model, as well as confocal laser scanning microscopy to study the free Mg(2+) spatial distribution in these cells. (31)P NMR spectroscopy did not prove to be effective for the determination of [Mg(2+)](i) in this particular case due to some special morphological and physiological properties of this cell type. A basal [Mg(2+)](i) value of 0.551 +/- 0.008 mM was found for these cells using fluorescence spectroscopy and the Mg(2+)-sensitive probe furaptra; this value falls in the concentration range reported in the literature for neurons from different sources. This technique proved to be an accurate and sensitive tool to determine the [Mg(2+)](i).lntraceilular free Mg(2+) seems to be essentially localized in the nucleus and around it, as shown by confocal microscopy with the Mg(2+)-sensitive probe Magnesium Green. It was not possible to derive any conclusion about free Mg(2+) localization inside the chromaffin granules and/or in the cytoplasm due to the lack of sufficient spatial resolution and to probe compartmentalization